2002
DOI: 10.1126/science.1067595
|View full text |Cite
|
Sign up to set email alerts
|

Micro/Nano Encapsulation via Electrified Coaxial Liquid Jets

Abstract: We report a method to generate steady coaxial jets of immiscible liquids with diameters in the range of micrometer/nanometer size. This compound jet is generated by the action of electro-hydrodynamic (EHD) forces with a diameter that ranges from tens of nanometers to tens of micrometers. The eventual jet breakup results in an aerosol of monodisperse compound droplets with the outer liquid surrounding or encapsulating the inner one. Following this approach, we have produced monodisperse capsules with diameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
586
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 937 publications
(598 citation statements)
references
References 29 publications
7
586
0
5
Order By: Relevance
“…It is extensively used for the synthesis of non-crosslinked particles via precipitation of polymers from their solutions [243][244][245][246][247], and a limited number of reports describe monomer polymerization [248][249][250], all of which being about nonporous particles. Loscertales et al [248] successfully electrified a coaxial jet composed of two immiscible liquids, the outer one being a commercial photo-polymerizable resin. Jet breakup resulted in monodisperse compound droplets and UV curing gave uniform submicron capsules with a liquid core.…”
Section: Other Techniquesmentioning
confidence: 99%
“…It is extensively used for the synthesis of non-crosslinked particles via precipitation of polymers from their solutions [243][244][245][246][247], and a limited number of reports describe monomer polymerization [248][249][250], all of which being about nonporous particles. Loscertales et al [248] successfully electrified a coaxial jet composed of two immiscible liquids, the outer one being a commercial photo-polymerizable resin. Jet breakup resulted in monodisperse compound droplets and UV curing gave uniform submicron capsules with a liquid core.…”
Section: Other Techniquesmentioning
confidence: 99%
“…It also allows encapsulating of core liquid and the production of tubes [12,13]. The sol-gel technique has been widely studied for the preparation of different forms including monoliths, powders, coatings, and fibers [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several research groups have reported synthesis of polymer particles in microfluidic reactors (Cohen et al 2001;Dendukuri et al 2005;Jeong et al 2005;Lewis et al 2005;Loscertales et al 2002;Nie et al 2005Nie et al , 2006Nisisako et al 2004;Seo et al 2005aSeo et al , 2005bTakeuchi et al 2005;Utada et al 2005;Xu et al 2005;Zhang et al 2006). The syntheses included a two-step process: (1) microfluidic emulsification of monomer or polymeric fluids, and (2) subsequent in-situ (on chip) solidification of the droplets by means of polymerization, gelation, or solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%